2011
DOI: 10.1136/jech.2010.128397
|View full text |Cite
|
Sign up to set email alerts
|

Marital status, living arrangement and mortality: does the association vary by gender?

Abstract: Evaluation of living arrangements is crucial for identifying and explaining gender differences in mortality risks by marital status. The impact of living alone and living with a partner seems to be different in men and women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
64
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(92 citation statements)
references
References 32 publications
21
64
1
2
Order By: Relevance
“…It is possible that even today, females are expected to be more giving and caring than males. However, a protective effect of marriage was found for both genders in the Swiss National Cohort, but the benefit of being married was stronger for men than for women (Staehelin et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that even today, females are expected to be more giving and caring than males. However, a protective effect of marriage was found for both genders in the Swiss National Cohort, but the benefit of being married was stronger for men than for women (Staehelin et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In general, the protective effect of marriage on mortality has been found to be stronger for men than for women (Davis et al, 1992;Gove, 1973;Jaffe et al, 2007;Kaplan and Kronick, 2006;Rendall et al, 2011;Scafato et al, 2008;Staehelin et al, 2012), though some studies have also reported contesting results (Lillard and Waite, 1995;Lund et al, 2002;Manzoli et al, 2007). The male advantage has often been attributed to the more important role of the social integration, support and control in marital relationships for men than women (Lillard and Waite, 1995;Umberson, 1992).…”
Section: Introductionmentioning
confidence: 90%
“…By contrast, the fitness benefits of heterosexual social relationships have been largely ignored. However, heterosexual bonds are protective in humans [1,4,24], and two pieces of evidence suggest that they may also be important in other mammals, especially in primates. First, two-thirds of primate genera exhibit permanent, yearround associations between adult males and females, including many non-monogamous species [25,26].…”
Section: Introductionmentioning
confidence: 99%